N-Fe2O3/nitrogen-sulfur double-doped graphene composite electrode material and preparation method thereof - WANG YING; XIE JIMIN; ZHANG MINGMEI; LI YUAN; PAN DENGHUI; YAN ZAOXUE; MA TIANJIAO (2017)
The invention provides an N-Fe2O3/nitrogen-sulfur double-doped graphene composite electrode material and a preparation method thereof. The method comprises: step one, oxidized graphene is added into a mixed solution of ethyl alcohol and ethylene glycol and ultrasonic dispersion is carried out to obtain a stable homogeneous dispersion solution A of oxidized graphene; step two, ferric nitrate nonalydrate and a nitrogen-sulfur source are added into the dispersion solution A obtained at the step one, and stirring is carried out uniformly to obtain a mixed solution B; step three, the mixed solution B obtained at the step two is transferred to a polytetrafluoroethylene hydrothermal reactor to carry out constant-temperature hydrothermal reaction, and after completion of reaction, a mixed solution C is obtained; and step four, suction filtration is carried out on the mixed solution B obtained at the step three and then cleaning and drying are carried out successively, thereby obtaining a product of N-Fe2O3/nitrogen-s